Not all minds that wander are lost: the importance of a balanced perspective on the mind-wandering state - Smallwood, Jonathan; Andrews-Hanna, Jessica (Frontiers in Psychology, 2013)
The waking mind is often occupied with mental contents that are minimally constrained by events in the here and now. These self-generated thoughts—e.g. mind-wandering or daydreaming—interfere with external task performance and can be a marker for unhappiness and even psychiatric problems. They also occupy our thoughts for upwards of half of the time, and under non-demanding conditions they (i) allow us to connect our past and future selves together, (ii) help us make successful long-term plans and (iii) can provide a source of creative inspiration. The lengths that the mind goes to self-generate thought, coupled with its apparent functionality, suggest that the mind places a higher priority on such cognition than on many other mental acts. Although mind-wandering may be unpleasant for the individual who experiences it and disruptive to the tasks of the moment, self-generated thought allows consciousness freedom from the here and now and so reflects a key evolutionary adaptation for the mind. Here we synthesize recent literature from cognitive and clinical psychology and propose two formal hypotheses that 1) highlight task context and thought content as critical factors that constrain the costs and benefits of self-generated thought and 2) provide direction on ways to investigate the costs and benefits from an impartial perspective.